COVID-19 morbidity in Afghanistan: a nationwide, population-based seroepidemiological study. Issue 7 (27th July 2022) - Saeedzai, Sayed Ataullah; Sahak, Mohammad Nadir; Arifi, Fatima; Abdelkreem Aly, Eman; Gurp, Margo van; White, Lisa J; Chen, Siyu; Barakat, Amal; Azim, Giti; Rasoly, Bahara; Safi, Soraya; Flegg, Jennifer A; et al.
Abstract : Objective: The primary objectives were to determine the magnitude of COVID-19 infections in the general population and age-specific cumulative incidence, as determined by seropositivity and clinical symptoms of COVID-19, and to determine the magnitude of asymptomatic or subclinical infections. Design, setting and participants: We describe a population-based, cross-sectional, age-stratified seroepidemiological study conducted throughout Afghanistan during June/July 2020. Participants were interviewed to complete a questionnaire, and rapid diagnostic tests were used to test for SARS-CoV-2 antibodies. This national study was conducted in eight regions of Afghanistan plus Kabul province, considered a separate region. The total sample size was 9514, and the number of participants required in each region was estimated proportionally to the population size of each region. For each region, 31–44 enumeration areas (EAs) were randomly selected, and a total of 360 clusters and 16 households per EA were selected using random sampling. To adjust the seroprevalence for test sensitivity and specificity, and seroreversion, Bernoulli's model methodology was used to infer the population exposure in Afghanistan. Outcome measures: The main outcome was to determine the prevalence of current or past COVID-19 infection. Results: The survey revealed that, to July 2020, around 10 million people in Afghanistan (31.5% of the population) had either current or previous COVID-19 infection. By age group, COVID-19 seroprevalence was reported to be 35.1% and 25.3% among participants aged ≥18 and 5–17 years, respectively. This implies that most of the population remained at risk of infection. However, a large proportion of the population had been infected in some localities, for example, Kabul province, where more than half of the population had been infected with COVID-19. Conclusion: As most of the population remained at risk of infection at the time of the study, any lifting of public health and social measures needed to be considered gradually.